Effect Of Different Feeding Percentages Of Golden Snail Paste On Growth And Survival Of Pearl Catfish (Clarias Gariepinus) Larvae - Moh. Rafif Baihaqi Falah; Rita Rostika; Gatot Hari Priowirjanto; Fittrie Meyllianawaty Pratiwy; Mohamad Hamdani (Universitas Islam Lamongan, 2026)
Feed is a primary factor influencing the growth and survival of pearl catfish larvae, therefore innovation in alternative feed that is efficient and highly nutritious is required. This study aims to analyze the effect of feeding paste made from golden snail flour (Pomacea canaliculata) at different percentages on the growth and survival of African catfish larvae (Clarias gariepinus). The method used was an experimental design with a Completely Randomized Design (CRD), consisting of three feeding treatments (5%, 10%, and 15% of biomass weight) with five replications, conducted over a 30-day rearing period. The observed parameters included survival rate (SR), absolute weight growth, absolute length growth, average daily growth (ADG), specific growth rate (SGR), and water quality. Data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that different feeding percentages had a highly significant effect (p > 0.05) on all parameters. The best treatment was obtained at a feeding rate of 10% of biomass weight, with a survival rate of 96.4%, absolute weight gain of 24.6 g, absolute length gain of 4.56 cm, ADG of 0.41 g/day, and SGR of 70%. Water quality during the study remained within optimal ranges, with temperatures of 24–27°C and pH levels of 7.8–8.5. Thus, feeding paste made from golden apple snail flour at 10% of biomass weight is the optimal dosage to improve the growth and survival of pearl catfish larvae.